Institutions and economic policies for pro-poor agricultural growth - Dorward, Andrew R.; Fan, Shenggen; Kydd, Jonathan; Lofgren, Hans; Morrison, Jamie; Poulton, Colin; Rao, Neetha; Smith, Laurence; Tchale, Hardwick; Thorat, Sukhadeo; Urey, Ian; Wobst, Peter (Wiley, 2004)
This paper draws together findings from different elements of a research project examining critical components of pro-poor agricultural growth and of policies that can promote such growth in poor rural economies in South Asia and Sub-Saharan Africa.